Turkish validity and reliability study of disease-related fear scale in patients with epilepsy - Turan, Gulcan Bahcecioglu; Ozer, Zulfunaz; Karman, Seda (Academic Press Inc Elsevier Science, 2023)
Objective: This study was conducted to examine the validity and reliability of the Turkish disease-related fear scale (D-RFS) for adult patients with epilepsy.Methods: This methodological study was conducted with 154 patients with epilepsy who were referred to the neurology clinic and outpatient clinic of Firat University Hospital between December 2021 and March 2022. Content and construct validity were evaluated after the scale was translated into Turkish. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were conducted for construct validity. Item analyses and internal consistency analyses were conducted for reliability. Convergent validity was also evaluated.Results: As a result of the evaluations and analyses, the content validity index of the scale was found to be 0.97. Exploratory factor analysis showed that the value of total variance explained by two factors was 74.77%. Factor loading of all items was found to be between 0.60 and 0.93. Cronbach's alpha values of the factors were found to be 0.97, while the total Cronbach's alpha value was found to be 0.95. As a result of the EFA and CFA, the 27-item, 2-factor disease-related fear scale was confirmed without changes to the original form of the scale. Good fit index values were obtained as a result of CFA.Conclusion: The Turkish version of the disease-related fear scale for adult patients with epilepsy is a valid and reliable measurement tool to evaluate the disease-related fear of adult patients with epilepsy and to use in clinical practice.(c) 2022 Elsevier Inc. All rights reserved.
Keywords: Validity; Reliability; Epilepsy; Fear; Patient